Slovene from a typological perspective: inherent and contact-induced developments, with particular attention to Celtic - Gvozdanović, Jadranka (Language typology and universals, 2003)
Der Artikel Slovene from a typological perspective: inherent and contact-induced developments, with particular attention to Celtic wurde am 1. September 2003 in der Zeitschrift STUF - Language Typology and Universals (Band 56, Heft 3) veröffentlicht.
Gesehen am 21.03.2025